Struktur Modal dan Pembiayaan BPRS di Indonesia - Multazam Mansyur Addury (Cakrawala: Jurnal Studi Islam, 2019)
The development of BPRS is expected to contribute to the market share of Islamic banking in Indonesia. This study aims to analyze the impact of capital structure on the BPRS financing. The object of this research is 164 BPRS in Indonesia, with a range of annual data from 2010 to 2017. The dependent variable is debt and equity-based financing (DEBF). The independent variable is measured using a debt to asset ratio (DAR) and debt to equity ratio (DER). In addition, this study also uses three control variables namely size, GDP growth rate, and provincial inflation. The data analysis technique used is panel data regression. The results show that the capital structure by DAR consistently had a positive and significant effect on the BPRS financing. Moreover, the capital structure by DER does not have a significant effect on the BPRS financing